2020
DOI: 10.3390/molecules25173977
|View full text |Cite
|
Sign up to set email alerts
|

A SF5 Derivative of Triphenylphosphine as an Electron-Poor Ligand Precursor for Rh and Ir Complexes

Abstract: The synthesis of the triarylphosphine, P(p-C6H4SF5)3 containing a SF5 group, has been achieved. The experimental and theoretical studies showed that P(p-C6H4SF5)3 is a weaker σ-donor when compared with other substituted triarylphosphines, which is consistent with the electron-withdrawing effect of the SF5 moiety. The studies also revealed a moderate air stability of the phosphine. The σ-donor capabilities of P(p-C6H4SF5)3 were estimated from the phosphorus-selenium coupling constant in SeP(p-C6H4SF5)3 and by D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Their X-ray data showed that SF 5 -triphenylphosphines have a larger Tolman cone angle compared to para-substituted phosphine ligands bearing N-(CH 3 ) 2 , CH 3 , OCH 3 , F, and CF 3 substituents. [112] Finally, the SF 5 group has been used as an electron acceptor in organic fluorophores. The group of Chan reported a series of push-pull dyes 156 a-d featuring an amine donor and SF 5 acceptor group.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…Their X-ray data showed that SF 5 -triphenylphosphines have a larger Tolman cone angle compared to para-substituted phosphine ligands bearing N-(CH 3 ) 2 , CH 3 , OCH 3 , F, and CF 3 substituents. [112] Finally, the SF 5 group has been used as an electron acceptor in organic fluorophores. The group of Chan reported a series of push-pull dyes 156 a-d featuring an amine donor and SF 5 acceptor group.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…The SF 5 moiety was incorporated as well in phosphine‐based ligands by Braun and co‐workers. Their X‐ray data showed that SF 5 ‐triphenylphosphines have a larger Tolman cone angle compared to para ‐substituted phosphine ligands bearing N(CH 3 ) 2 , CH 3 , OCH 3 , F, and CF 3 substituents [112] …”
Section: Applications Of Sf5‐containing Compounds and Analogsmentioning
confidence: 99%
“…Professor Todd B. Marder has contributed significantly to expand the scope of boron chemistry, and it is an honor to celebrate his achievements, and mark his 65th birthday with a Special Issue of Molecules : “Boron in Catalysis and Materials Chemistry: A Themed Issue in Honor of Professor Todd B. Marder on the Occasion of His 65th Birthday”. It includes excellent review articles on conjugated N^C-organoboron materials, and tri(boryl)-alkanes and -alkenes as versatile reagents in organic synthesis [ 31 , 32 ], and research articles depicting diversity [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ], as noted in the research interests of Professor Marder. We thank all the authors for joining us to congratulate Todd, and for making this issue a successful one through their excellent scientific contributions.…”
mentioning
confidence: 99%